Re-situating Ourselves: Learning from Community Organizations’ Stories of Conflict, Challenge and Failure - Susan J. Bracken (Adult Education Research Conference, 2007)
This paper presents a preliminary framework for examining a feminist community group’s day to day conflicts, challenges and practical dilemmas, labeled as doublebinds. The research identifies the most commonly experienced dilemmas within a feminist community organization. It then discusses observed coping strategies of selection, vacillation, and source splitting.